PENERIMAAN PANELIS TERHADAP TEH HERBAL DARI KULIT BUAH MANGGIS ( Garcinia mangostana L. ) DENGAN PERLAKUAN SUHU PENGERINGAN - NOVIAR HARUN '; RASWEN EFENDI '; LASMA SIMANJUNTAK ' (Universitas Riau, 2014)
The processing of mangosteen rind is still less than optimal, so one of processing mangosteen rind ismaking herbal tea. The purpose of research is drying mangosteen rind with best quality and knowing theacceptance of panelists from herbal tea of mangosteen rind. Research conducted using a CompletelyRandomized Design (CRD) with 4 treatments and 4 replications. Each treatment is using drying for 3 hoursat different temperatures, namely 75°C, 80°C, 85°C and 90°C. Parameters measured were water content, ashcontent, crude fiber, antioxidants, toxicity and organoleptic. The result showed the drying temperaturesignificantly affect the water content, crude fiber, organoleptic and not significantly to ash content. Thebest treatment is drying at 85 ° C with a water content value 7.98; 4,129 ash content; crude fiber 7863;antioxidant 3.95 × 10-34; toxicity of 34.67 and 0.92 overall acceptance.Keywords: mangosteen, drying temperature, mangosteen rind, herbal tea